The Effects of Ground Fire on Tree Population in a Secondary Forest in South Western Nigeria - Kayode, J.; Isichei, A. O. (2014)
The changes in the tree population in a 50m x 50m rain forest plot on the campus of Obafemi Awolowo University, Ile-Ife, Nigeria, six years after it was burnt were assessed by comparing the results obtained in 1989 with those of January 1983, just before the plot was burnt and those of April 1984, a year after the plot was burnt. The number of tree species and the numbers of tree individuals had increased between 1984 and 1989 by 10%. Manihot glaziovii Mill-Arg the most abundant species in the plot in 1984 still maintain its status but its density decreased from 81% in 1984 to 61% in 1989 while Funtumia elastica (Preuss) stapf showed a remarkable increase from 8% in 1984 to 88% in 1989. Other species present in the plot showed a little net change in population over the same period. These observations demonstrated successional trend in gap replacement. It is considered that population dynamics is better studied by monitoring plot over time as the best was of studying plant succession.